The West Wing. The complete third season [videorecording (DVD)] - Sheen, Martin; Lowe, Rob; Janney, Allison; Channing, Stockard; Hill, Dulé; Moloney, Janel, 1969-; Schiff, Richard, 1955-; Spencer, John, 1946-2005; Whitford, Bradley (Warner Bros. Entertainment, 2004)
The 22-episode third season whose storylines include the investigation into the alleged cover-up of President Barlet's illness, the early bid for a second term and confrontations with global terrorism. Reel- and real-life events profoundly intersect in the historic Isaac and Ishmael episode made in the wake of the terrorist attacks of September 11, 2001. And must-see bonus features include a special The West Wing look at the executive branch featuring interviews with former U.S. Presidents and staff.